Effects of changes in arterial pressure on organ perfusion during septic shock - Thooft, Aurélie (BioMed Central, 2011)
INTRODUCTION: Septic shock is characterized by altered tissue perfusion associated with persistent arterial hypotension. Vasopressor therapy is generally required to restore organ perfusion but the optimal mean arterial pressure (MAP) that should be targeted is uncertain. The aim of this study was to assess the effects of increasing MAP using norepinephrine (NE) on hemodynamic and metabolic variables and on microvascular reactivity in patients with septic shock. METHODS: This was a single center, prospective, interventional study conducted in the medico-surgical intensive care unit of a university hospital. Thirteen patients in septic shock for less than 48 hours who required NE administration were included. NE doses were adjusted to obtain MAPs of 65, 75, 85 and (back to) 65 mmHg. In addition to hemodynamic and metabolic variables, we measured thenar muscle oxygen saturation (StO(2)), using near infrared spectroscopy (NIRS), with serial vaso-occlusive tests (VOTs) on the upper arm. We also evaluated the sublingual microcirculation using sidestream dark field (SDF) imaging in 6 of the patients. RESULTS: Increasing NE dose was associated with an increase in cardiac output (from 6.1 to 6.7 l/min, P<0.05) and mixed venous oxygen saturation (SvO(2), from 70.6 to 75.9%, P<0.05). Oxygen consumption (VO(2)) remained stable, but blood lactate levels decreased. There was a significant increase in the ascending slope of StO(2 )(from 111 to 177%/min, P<0.05) after VOTs. SDF imaging showed an increase in perfused vessel density (PVD, from 11.0 to 13.2 n/mm, P<0.05) and in microvascular flow index (MFI, from 2.4 to 2.9, P<0.05). CONCLUSIONS: In this series of patients with septic shock, increasing MAP above 65 mmHg with NE was associated with increased cardiac output, improved microvascular function, and decreased blood lactate concentrations. The microvascular response varied among patients suggesting that individualization of blood pressure targets may be warranted.